Evaluasi Pengalaman Pengguna Pada Aplikasi Mobile Messenger Menggunakan Metode UX Curve (Studi Kasus pada Aplikasi LINE dan WhatsApp) - Novia Fanny Salsabila; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Messanger is a application to send a message which makes it easy for users to communicate with each other. Two of the applications that has a many users around the world is LINE and WhatsApp. This study aims to compare two mobile messanger applications for evaluating long-term user experience. Data collected was produce 200 curves, 100 curves for each application, from the 100 curves the divided into 5 points of view; general UX, attractiveness, ease of use, utility, and degree of usage which 20 curves for each point of view. The curves then combined into a graph and categorized based trends of curve; improving, deteriorating and stable. For LINE application, they has a total 27 improving curves, 7 deteriorating curves, and 67 stable curves. And for WhatsApp application, they has a total 8 improving curves, 18 deteriorating curves and 74 stable curves. Other than that, the reasons of change counted for measure what are the changes of the curve they draw. The reasons consists of positive and negative, then categorized into pragmatic and hedonic perceptions. The relation with user satisfaction and recommendation seen by connecting the attractiveness curve and results of final questionnaire. User satisfaction can be seen with how the users recommended the applications to their friends. 3 of 20 respondents choose LINE application for recommended to their friends, the rest answers that depends on their need.